Differentiation of the World Hop Collection by Means of the Low Weight Molecular Polyphenols - Kammhuber, Klaus (BrewingScience, 2012)
Hop has three groups of variety-specific ingredients. These are the bitter substances, the essential oils and also some low molecular weight polyphenols like the flavonoids. In this work the focus was mainly on the composition of the quercetin- and kaempferol-glycosides, because these compounds are suitable to differentiate varieties. Initial work focused on the development of convenient methods for sample preparation and HPLC-analysis. Then nearly the whole available world hop collection (121 different varieties from 17 countries) was analysed. The data were evaluated by a principal component analysis to make differences and similarities visible. Some varieties are clearly distinguished from their polyphenol composition, while others, especially the old land races, were barely distinguishable from each other.